TINGKAT VO2MAX PADA ATLET SEPAKBOLA (SSB) BLOK 6 JUNIOR U-15 KABUPATEN ACEH SINGKIL TAHUN 2019 - Budi Rahmanto; Alfian Rinaldy; Masri Masri (Jurnal Dedikasi Pendidikan, 2021)
The results of observations made on football athletes Block 6 junior U-15, found problems that are first, low ability VO2Max athletes, this is because players often appear to experience fatigue when the game is rolling especially in the second half' Second, not the maximum coaching exercises in accordance with the rules of training that lead to physical coaching. The purpose of the study was to find out the level of VO2Max. The research approach is quantitative approach and descriptive type of research. The total sampling population is a sample of 16 Blok 6 Junior U-15 football athletes in Aceh Singkil District in 2019. Data collection is done by Bleep Test or multy stage running test with a distance of 20 meters gradually back and forth. Data analysis uses average formulas and frequency distributions. The results of the study found that the VO2Max level of SSB Block 6 Junior U-15 football athletes in Aceh Singkil District in 2019 obtained an average Bleep test score of 38.83 in the "medium" category. Of the 16 athletes, 16 athletes did not reach the "Special" category, nor the "Good" category, 10 people (62.50%) category "Medium", 5 people (31.25%) in the category of "Less" and 1 person (6.25%) samples belonging to the category "Very Less". The conclusion of this research is VO2Max level in SSB Block 6 Junior U-15 football athletes in Aceh Singkil District in 2019 in the "medium" category. This indicates that there is still need to be an evaluation after coaching further exercises about VO2Max for SSB Block 6 Junior U-15 football athletes in Aceh Singkil Regency